“I learned to trust myself”. An oral history of professional nurses’ wartime practice in Finnmark - Immonen, Ingrid (Nordlit, 2015)
As we can see in war areas today, health care systems and especially hospitals can be considered as a safety net for the civilian population. This was also the case of civilian health care institutions, nurses and medical practitioners in the sparsely populated areas in Finnmark and Northern part of Troms during World War II. Nurses are, and were, the largest group of health professionals. Most nurses worked in small communities and institutions over the large province, and their efforts have been under-communicated. Through interviews, mainly with nurses but also with catholic Sisters in Hammerfest and Tromsø as well as members of families with sick persons, we get a picture of daily work as well as work in extreme conditions. There was a need for creative solutions when the basics of water, food, supplies and medicine were lacking, when nursing care was being provided in bomb shelters or during escape. There is also the issue of ethics while nursing enemies as well as friends. The physical and mental demands on the nurses were extreme. By detailing the war’s challenges to nursing, its challenges to civilian life are at the same time conveyed.